Design and implementation of broadcasting system for selective contents considering interruption time. (24th April 2020) - Fujita, Takuro; Gotoh, Yusuke
Owing the recent popularisation of digital broadcasting, selective contents broadcasting has attracted much attention. In selective contents broadcasting, although the server delivers contents based on their preferences, users may experience the interruption time while playing their selected contents. To reduce this interruption time, many researchers have proposed scheduling methods. However, since these scheduling methods evaluated the interruption time in simulation environments, we need to evaluate them in network environments. In this paper, we propose a broadcasting system of selective contents and evaluate its effectiveness in network environments.